EXPERIMENTAL STUDIES OF AN ALGORITHM FOR MINIMIZING THE IDLE TOOL MOVES WHEN MILLING COMPLEX SURFACES ON TRIAXIAL CNC MACHINE TOOLS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The idle running times of the working units of a machine tool are the sum of the idle running times for the tool change and for changing the section uder treatment. The time, spent on idle running is the extra machining time. A large number of milling cutters are used for purely mechanical machining of details with complex surfaces and for a significant number of machined sections, where the complex surface is broken as a rule. This leads to an increase in the extra time for treatment. Reducing the auxiliary time in machining the parts will significantly increase the productivity of the actual milling process. When modeling the process of machining details with complex surfaces on triaxial milling machines, the optimization of the sequence of moves will allow to reduce the idle running time by up to 50% without causing deterioration in the quality of the surface layer. In modern production a method is needed, which would allow to automatically and quickly enough make a choice of an optimal option for a sequence of performing tool moves while taking into account the durability of the metal cutting tool.